Impacts of barrage flushing and flooding-in operations on saline intrusion upstream - Law, I.N. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This research looks into the effects of barrage flushing and flooding-in operations on upstream salinity versus discharge over time. Water samples for salinity levels were collected over a period of 33 hours from two locations upstream of Sarawak Barrage, i.e., at i.5 km and 6 km.